Long-term efficacy and safety of a new botulinum toxin type A preparation in mouse gastrocnemius muscle. (November 2020) - Na, Jungtae; Lee, Esther; Kim, Yu-jin; Choi, Mi Ji; Kim, Su-Young; Nam, Jeong Sun; Yun, Bum Jin; Kim, Beom Joon
Abstract: A new type A botulinum toxin (BoNT/A) preparation, JTM201 (NCBI chromosomal DNA ID: CP046450), has been developed, which comprises 900-kDa complexed toxin purified from Clostridium botulinum (strain: NCTC13319), but its safety and efficacy have not yet been evaluated. The purpose of this study was to evaluate the long-term efficacy and safety of JTM201 at different concentrations in comparison to another commercially available BoNT/A product, Botox® (onabotulinumtoxin A, ONA), using a mouse model. The LD50 of JTM201 was similar to that of ONA, but the intrinsic activity of JTM201 was higher than that of ONA. Functional recovery of the nerves and muscles in SKH-1 mice after administration of the two BoNT/A preparations (JTM201 and ONA) to the right gastrocnemius muscle was observed over 24 weeks. In addition, JTM201 did not induce any skin or muscle inflammatory response in 24 weeks. Paralysis induced by neurotransmitter blockade after JTM201 administration was comparable to that of ONA treatment. Both muscle weight and volume decreased in a concentration-dependent manner following JTM201 or ONA toxin injection until week 4. Reduced muscle fiber size due to atrophy and consequent fibrosis were detected following injection of JTM201 or ONA. Moreover, we assessed the extent of diffusion of JTM201 or ONA to the tibialis anterior and quadriceps femoris muscles, demonstrating limited diffusion to off-target muscles. In conclusion, JTM201 demonstrated long-term efficacy and safety equivalent to those of ONA based on compound muscle action potential, muscle volume, and histology analyses. These data suggest that JTM201 is a new BoNT/A formulation with safety and efficacy comparable to those of ONA. Highlights: JTM201 was compared to onabotulinumtoxin A (ONA) in in vivo models. JTM201 showed safety and efficacy comparable to that of ONA (Botox). LD50 of JTM201 was similar to that of ONA, but intrinsic activity of JTM201 was higher than that of ONA. JTM201 did not diffuse to the adjacent muscles at the same dose as ONA.